Knowledge and attitude toward Autism Spectrum Disorder (ASD) among students in Faculty of Education UiTM Selangor, Puncak Alam Campus / Haziqah Ismail, Siti Nur Amiera Shafeza Ibrahim and Roslinda Isa - Ismail, Haziqah; Ibrahim, Siti Nur Amiera Shafeza; Isa, Roslinda (Faculty of Health Sciences, Universiti Teknologi MARA, 2021)
Introduction: Delays in identifying autism lead to lack of support and therapy for the child, who may not develop basic social skills, speak or behave in ways that cause problems. Aside from early detection, screening among health care providers, school teachers should also be involved in recognizing autistic traits in children. Thus, late diagnosis can be avoided. Objective: To assess the level of knowledge and attitude toward Autism Spectrum Disorder (ASD) among students in the faculty of Education at UiTM Puncak Alam Campus. Method: A cross-sectional survey was done utilising an online questionnaire via Google link and completed by 213 students from faculty of Education UiTM Puncak Alam. Questionnaire was divided on 3 parts: Part A demographic data, part B Knowledge and Part C Attitude on ASD. Result: 89.2% of students had good knowledge and 10.8% had poor knowledge on autism. Furthermore, 93% had positive attitude, while 7% had negative attitude toward ASD. This study showed no significant relationship between the students’ level of knowledge and attitude towards ASD (p=1.000). Conclusion: This study indicates good knowledge and a positive attitude about ASD. In the future, more autism education to students and teachers should be provided for better understanding regarding autism.